Design of a Mini Bank Service System for Regional Public Service Agencies (BLUD) in Vocational High Schools - Yulius Hari; Darmanto Darmanto; Minny Elisa Yanggah; Melvie Paramitha (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study is aims to help Vocational high schools, which are partners in this activity, are also focusing on the rapid development of BLUD so that they can become financially independent and develop their educational institutions through their own efforts. With the development of this mini-bank, it is necessary to develop an information system that can assist the partner in keeping track of all the management and transaction flows that take place in this her BLUD. Here, this non-profit activity is taking place specifically for partners to realize the system that supports her BLUD Minibank. This non-profit activity has resulted in optimized efficiency of BLUD Minibank transactions and enhanced partner skills in the use of information technology